Repurposing effect of cardiovascular-metabolic drug to increase lifespan: a systematic review of animal studies and current clinical trial progress - Barinda, Agian Jeffilano; Hardi, Harri; Louisa, Melva; Khatimah, Nurul Gusti; Marliau, Rheza Meida; Felix, Immanuel; Fadhillah, Muhamad Rizqy; Jamal, Arief Kurniawan (Frontiers in Pharmacology, 2024)
With the increase in life expectancy, aging has emerged as a significant health concern. Due to its various mechanisms of action, cardiometabolic drugs are often repurposed for other indications, including aging. This systematic review analyzed and highlighted the repositioning potential of cardiometabolic drugs to increase lifespan as an aging parameter in animal studies and supplemented by information from current clinical trial registries. Systematic searching in animal studies was performed based on PICO: "animal", "cardiometabolic drug", and "lifespan". All clinical trial registries were also searched from the WHO International Clinical Trial Registry Platform (ICTRP). Analysis of 49 animal trials and 10 clinical trial registries show that various cardiovascular and metabolic drugs have the potential to target lifespan. Metformin, acarbose, and aspirin are the three most studied drugs in animal trials. Aspirin and acarbose are the promising ones, whereas metformin exhibits various results. In clinical trial registries, metformin, omega-3 fatty acid, acarbose, and atorvastatin are currently cardiometabolic drugs that are repurposed to target aging. Published clinical trial results show great potential for omega-3 and metformin in healthspan.Systematic review registration: crd.york.ac.uk/prospero/display_record.php?RecordID=457358, identifier: CRD42023457358